Pollination and breeding system of the enigmatic South African parasitic plant Mystropetalon thomii (Mystropetalaceae): rodents welcome, but not needed. (26th June 2017) - Hobbhahn, N.; Steenhuisen, S.‐L.; Olsen, T.; Midgley, J. J.; Johnson, S. D.
Abstract: Unrelated plants adapted to particular pollinator types tend to exhibit convergent evolution in floral traits. However, inferences about likely pollinators from 'pollination syndromes' can be problematic due to trait overlap among some syndromes and unusual floral architecture in some lineages. An example is the rare South African parasitic plant Mystropetalon thomii (Mystropetalaceae), which has highly unusual brush‐like inflorescences that exhibit features of both bird and rodent pollination syndromes. We used camera traps to record flower visitors, quantified floral spectral reflectance and nectar and scent production, experimentally determined self‐compatibility and breeding system, and studied pollen dispersal using fluorescent dyes. The dark‐red inflorescences are usually monoecious, with female flowers maturing before male flowers, but some inflorescences are purely female (gynoecious). Inflorescences were visited intensively by several rodent species that carried large pollen loads, while visits by birds were extremely rare. Rodents prefer male‐ over female‐phase inflorescences, likely because of the male flowers' higher nectar and scent production. The floral scent contains several compounds known to attract rodents. Despite the obvious pollen transfer by rodents, we found that flowers on both monoecious and gynoecious inflorescences readily set seed in the absence of rodents and even when all flower visitors are excluded. Our findings suggest that seed production occurs at least partially through apomixis and that M. thomii is not ecologically dependent on its rodent pollinators. Our study adds another species and family to the growing list of rodent‐pollinated plants, thus contributing to our understanding of the floral traits associated with pollination by non‐flying mammals.